The effect of washing and wearing on sports bra function - Wakefield-Scurr, J.; Hamilton, C.; Reeves, K.; Jones, M.; Jones, B. (Sports Biomechanics, 2022)
Sports bras provide support by restricting breast motion during exercise, which may prevent damage to breast structures. Laundering affects the mechanical properties of some sports bra materials. Bra function on the wearer after washing is unreported, meaning sports bra durability is unknown. This intervention study compared subjective and objective performance of sports bras that were washed, and worn/washed, to a control. Twenty-two females were assigned three identical sports bras; control, washed and worn/washed (washed after 60-min wear). Pre-intervention: breast position was recorded while standing and running in each bra. Comfort, fit and aesthetics were rated. Intervention: participants undertook their normal exercise in their worn/washed bra. Post-intervention: after 25 washes (n = 19), pre-intervention testing was repeated. Breast volume and control bra motion were consistent pre/post-intervention; however, post-intervention breast motion increased (20% mediolaterally, 16% superioinferiorly) in washed bras and (32% mediolaterally, 25% superioinferiorly) worn/washed bras. Post-intervention washed, and worn/washed bras were perceived as less supportive and washed bras less comfortable than worn/washed bras. Sports bra support reduced after 25 washes; this was compounded by wear. Participants detected reduced support, but comfort was sustained, suggesting replacement may not be considered. Guidelines on sports bra durability are recommended for breast health.